Identifying Learning Styles of Biology Education Students - Ami, Mucharommah Sartika; Yanti, Norma Linda (APPLICATION: Applied science in Learning Research, 2024)
It is necessary to identify student learning styles, especially by lecturers, to understand student characteristics before preparing learning plans. This research aims to identify types of learning styles of biology education students at Universitas KH. A. Wahab Hasbullah. The method used is a survey with an instrument in the form of a learning style questionnaire. The total population of biology education students is 67 and the respondents who filled out the questionnaire were 48 students. The data obtained was analyzed descriptively. There are five types of learning styles identified from the results of this research, namely visual, auditory, kinesthetic, visual auditory, and visual kinesthetic. The learning style that most students have is auditory, both male and female students. Only female students showed a combination learning style, namely visual auditory and visual kinesthetic.